Mindfulness-based intervention on treatment adherence in hemodialysis patients: a randomized controlled trial - Fatemeh Mirzaei Jirandehi; Seyedehzahra Hosseinigolafshani; Mehdi Ranjbaran; Mohammad Reza Sheikhi (BMC Complementary Medicine and Therapies, 2026)
Abstract Background Treatment adherence remains a persistent and critical clinical challenge among patients undergoing maintenance hemodialysis. In Iranian populations, reported rates of non-adherence vary significantly, ranging from 2% to 87%; this disparity reflects inconsistencies in measurement methodologies, clinical contexts, and adherence domains. Although mindfulness-based interventions (MBIs) have demonstrated potential for enhancing chronic disease self-management, their efficacy in improving treatment adherence specifically within the hemodialysis population remains under-researched. Objective The aim of this study was to evaluate the efficacy of a mindfulness-based intervention on treatment adherence among patients undergoing maintenance hemodialysis. Methods A randomized controlled trial was conducted at Bu-Ali Sina Educational Medical Center in Qazvin, Iran, between November 2024 and January 2025. A total of 78 eligible hemodialysis patients were assigned to either the intervention or control group via block randomization, with 39 participants allocated to each group. The intervention group participated in eight weekly mindfulness training sessions, each lasting 30–45 min, which were delivered during hemodialysis sessions and adapted from Kabat-Zinn’s mindfulness-based protocol. The control group received routine clinical care. The primary outcome, treatment adherence, was assessed using the End-Stage Renal Disease (ESRD) Adherence Questionnaire at baseline, immediately following the intervention, and at a one-month follow-up. Data were analyzed to examine between-group differences over time and group-by-time interaction effects. Results Of the 78 randomized participants, 70 completed the study: 36 in the intervention group and 34 in the control group. Baseline treatment adherence scores did not differ significantly between the intervention and control groups (862.83 ± 166.29 versus 842.82 ± 187.80; p = .638). The intervention group demonstrated a significantly greater improvement in adherence change scores compared to the control group at the one-month follow-up ( p = .005). However, the group × time interaction was not significant ( P = .223, Partial Eta² = 0.022), suggesting no differential change between groups across time points. Conclusions The mindfulness-based intervention did not demonstrate a significant overall effect on treatment adherence in the repeated-measures analysis; however, exploratory analyses indicated greater improvement in the intervention group at follow-up, particularly in dietary adherence. These findings suggest that mindfulness may be a feasible adjunct to routine nursing care for supporting selected aspects of self-management in hemodialysis patients. Nevertheless, broader improvements across all adherence domains, including fluid restriction, medication adherence, and dialysis attendance, may require additional domain-specific or multimodal interventions. Trial registration Iranian Registry of Clinical Trials IRCT20240917063074N1. Registered on 22 October 2024.